(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article talks about the depiction of a child’s life in the stories of N. Norkabilov, "Oriyat", "Erkak", “Hesh” the emergence of a conflict in the story, and the artistic quality of detail in the work.